Effect of Mango Peel and Pulp Extract on the Quality Characteristics of Chicken Nuggets - Kadakadiyavar, P.; Ambadkar, R. K.; Rathod, K. S. (Journal of Meat Science, 2016)
In the present study the effects of mango peel extract (MPeE), mango pulp extract (MPuE) and butylated hydroxyanisole (BHA) on the keeping quality of chicken nuggets was assessed. The results indicated significantly lower (p
Keywords: Mango peel extract; Mango pulp extract; BH